Cabo Verde : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Cabo Verde. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that the economic growth of Cabo Verde in 2015 stagnated at 1.5 percent, slightly below the 1.9 percent registered in 2014. Tourism recovered and remittances remained robust, but foreign direct investment (FDI) and public investment slowed. The unemployment rate declined to 12.4 percent, as did youth unemployment, which nevertheless remained high at 28.6 percent. Consumer price inflation remained muted owing to lower food and energy prices, averaging 0.1 percent for 2015. In 2016, growth is forecast to recover to 3.2 percent supported by FDI, domestic demand, agriculture, and tourism, which should benefit from the mild upswing in Europe.